2003
DOI: 10.1177/0146167203255765
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests of an Attitudinal Theory of the Gender Gap in Voting

Abstract: This research examined the hypothesis that gender gaps in voting stem from differences in the extent to which men and women agree with candidates' issue stances. Two initial experiments portraying candidates by their sex and attitudes and a third experiment that also included information about political party produced the predicted attitudinal gender-congeniality effect: Participants of each sex reported greater likelihood, compared with participants of the other sex, of voting for the candidate who endorsed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…For example, research by Eagly, Diekman, Scheider, and Kulesa (2003) found that individuals tend to vote for candidates who endorse policies supportive of the interests of their gender, regardless of the candidate's sex. However, when a candidate's attitude was not clearly congenial to only women or only men, a gender‐matching preference for candidates of one's own gender emerged such that women were more likely to vote for a female candidate and men were more likely to vote for a male candidate (Eagly et al, 2003, Study 1). Hoyt, Simon, and Reid (in press) also found a gender‐bias, but only when individuals' mortality was made salient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research by Eagly, Diekman, Scheider, and Kulesa (2003) found that individuals tend to vote for candidates who endorse policies supportive of the interests of their gender, regardless of the candidate's sex. However, when a candidate's attitude was not clearly congenial to only women or only men, a gender‐matching preference for candidates of one's own gender emerged such that women were more likely to vote for a female candidate and men were more likely to vote for a male candidate (Eagly et al, 2003, Study 1). Hoyt, Simon, and Reid (in press) also found a gender‐bias, but only when individuals' mortality was made salient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a review of actual congressional elections have found ''no difference between the success rates for men and women in general elections'' (Seltzer, Newman, & Leighton, 1997, p. 79) and ''the presence of women candidates, in most cases, does not influence the public in one particular direction'' (Dolan, 2004, p. 154). Moreover, some research shows that a candidate's gender may not have a direct influence on the likelihood of an individual voting for a candidate in U.S. House elections (Eagly, Diekman, Schneider, & Kulesa, 2003). Yet, this research also found an ''attitude congeniality'' effect, where women (and Democratic men) were more likely to vote for candidates expressing women-congenial attitudes (Eagly et al, 2003; see also Hernson, Lay, & Stokes, 2003).…”
mentioning
confidence: 99%
“…Moreover, some research shows that a candidate's gender may not have a direct influence on the likelihood of an individual voting for a candidate in U.S. House elections (Eagly, Diekman, Schneider, & Kulesa, 2003). Yet, this research also found an ''attitude congeniality'' effect, where women (and Democratic men) were more likely to vote for candidates expressing women-congenial attitudes (Eagly et al, 2003; see also Hernson, Lay, & Stokes, 2003).…”
mentioning
confidence: 99%
“…The target was a candidate for the state House of Representatives and espoused three neutral policy stances that were held constant across conditions. To reinforce the manipulation of candidate sex, gendered pronouns were repeated seven times during the task (for a similar manipulation of candidate sex, see Brown, Diekman, & Schneider, 2011;Eagly, Diekman, Schneider, & Kulesa, 2003;see Appendix A). No additional candidate information was provided.…”
Section: Independent Variablesmentioning
confidence: 99%